THE EFFECT OF VILLAGE FUNDS AND VILLAGE FUND ALLOCATIONS ON POVERTY LEVELS IN PEUREULAK SUB-DISTRICT, EAST ACEH DISTRICT. - Rahmawati, Rahmawati; Mellita Sari, Cut Putri (Journal of Malikussaleh Public Economics, 2024)
The reason for this study was to decide how much impact the Town Asset and Town Asset Distribution have on the Neediness Level in Peureulak Area, East Aceh Rule. Eviews 10 is utilized to consolidate Cross-Segment information with Time Series in this review. This study used panel data in five villages in the East Aceh Regency's Peureulak District from 2015 to 2022. The chosen panel model, the Random Effect Model (REM), was tested and found to have a positive, which had a significant impact on the poverty rate in five villages in the East Aceh Regency's Peureulak District, and a negative, which had no impact at all. The consequences of synchronous testing show that the factors of town assets and what they are dispersed have a huge mean for on the destitution rate in five towns in the Peureulak Subdistrict of the East Aceh Locale.